2017
DOI: 10.1021/acs.jced.7b00181
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Rheological Behavior of 1-Ethyl-3-methylimidazolium n-Hexylsulfate and Trihexyl(tetradecyl)phosphonium Tris(pentafluoroethyl)trifluorophosphate

Abstract: Ionic liquids have been broadly studied in the last decade for being used as lubricants or lubricant additives. The rheological characterization of these fluids is very important in Newtonian behaviour in the studied conditions. The trifluorophosphate IL has strong pressure-viscosity dependence whereas for the other IL this dependence is quite slight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…55 Regueira et al also reported the rheological characterization of two different ILs ([C 2 C 1 im][C 6 SO 4 ] and [P 6,6,6,14 ][(C 2 F 5 ) 3 PF 3 ]) and the results were compared with the reference oils used for lubrication. 62 Newtonian behavior was observed for both ILs and the viscosity values of [C 2 C 1 im]-[C 6 SO 4 ] were closer to that of polyalkylene glycol.…”
Section: ■ Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…55 Regueira et al also reported the rheological characterization of two different ILs ([C 2 C 1 im][C 6 SO 4 ] and [P 6,6,6,14 ][(C 2 F 5 ) 3 PF 3 ]) and the results were compared with the reference oils used for lubrication. 62 Newtonian behavior was observed for both ILs and the viscosity values of [C 2 C 1 im]-[C 6 SO 4 ] were closer to that of polyalkylene glycol.…”
Section: ■ Introductionmentioning
confidence: 77%
“…Arrhenius law was observed to be appropriate to fit the viscosity–temperature data of aprotic ILs, whereas the Vogel–Tamman–Fulcher relation was more suited to ILs having functionalized or a symmetric cation. , The viscosity and viscoelastic properties of ILs also decreased at the transition temperature for liquid crystalline to isotropic phase transformation . Regueira et al also reported the rheological characterization of two different ILs ([C 2 C 1 im]­[C 6 SO 4 ] and [P 6,6,6,14 ]­[(C 2 F 5 ) 3 PF 3 ]) and the results were compared with the reference oils used for lubrication . Newtonian behavior was observed for both ILs and the viscosity values of [C 2 C 1 im]­[C 6 SO 4 ] were closer to that of polyalkylene glycol.…”
Section: Rheology Of Pure Ionic Liquids (Ils)mentioning
confidence: 99%
“…The rightmost expression gives Δ V ‡ in terms of the modified VFT coefficients of eq . α η, p is an important parameter in tribology for the calculation of lubrication film thickness, and there is some interest in the use of ionic liquids as lubricants though the corrosive nature of [BMIM]­[Ac] probably precludes its use for this purpose. Isotherms (323.15 K (50 °C)) for other [BMIM] + ionic liquids are shown for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…2012-051-1-100; 2013-05-15) “International standard for viscosity at temperatures up to 473 K and pressures below 200 MPa” was launched with the goal to identify and characterize a reference fluid with a viscosity around 20 mPa·s at those limiting temperature and pressure conditions. These conditions are now encountered routinely in the exploitation of fossil fuel reservoirs and in lubrication In a series of papers, the candidature of tris­(2-ethylhexyl) trimellitate (TOTM) has been considered for such a fluid. Most recently, an article was published that provided the results of an international collaborative study to establish standard reference values for the viscosity, density, surface tension, and rheological character of TOTM.…”
Section: Introductionmentioning
confidence: 99%